2012
DOI: 10.1038/npp.2012.225
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid Receptor and FKBP5 Expression Is Altered Following Exposure to Chronic Stress: Modulation by Antidepressant Treatment

Abstract: Major depression is thought to originate from the interaction between susceptibility genes and adverse environmental events, in particular stress. The hypothalamus-pituitary-adrenal (HPA) axis is the major system involved in stress response and its dysregulation is an important element in the pathogenesis of depression. The stress response is therefore finely tuned through a series of mechanisms that control the trafficking of glucocorticoid receptors (GRs) to the nucleus, including binding to the chaperone pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
110
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 159 publications
(122 citation statements)
references
References 46 publications
11
110
1
Order By: Relevance
“…In the case of repeated stress such as CMS exposure, the effects on vSub-NAc plasticity may result from long-term changes in BLA GR and CB1 activity. In support of this, previous studies found that animals exposed to CMS show alterations in the expression of GRs and CB1 receptors in the hippocampus, NAc, and PFC (Bortolato et al, 2007;Guidotti et al, 2013;Hill et al, 2008).…”
Section: Cms and Win55212-2 Effects On Plasticitysupporting
confidence: 66%
“…In the case of repeated stress such as CMS exposure, the effects on vSub-NAc plasticity may result from long-term changes in BLA GR and CB1 activity. In support of this, previous studies found that animals exposed to CMS show alterations in the expression of GRs and CB1 receptors in the hippocampus, NAc, and PFC (Bortolato et al, 2007;Guidotti et al, 2013;Hill et al, 2008).…”
Section: Cms and Win55212-2 Effects On Plasticitysupporting
confidence: 66%
“…Specifically, the GR-mediated increase in SGK1 expression upon cortisol treatment further enhances GR phosphorylation at the serine residues S203 and S211, which are phosphorylation sites known to facilitate nuclear translocation of the receptor (20,21). Accordingly, SGK1 enhances and maintains GR nuclear translocation even after cortisol withdrawal.…”
Section: Discussionmentioning
confidence: 99%
“…S7), ChIP, and RNA extraction were performed using published methods (33). Analysis by qPCR was conducted using primer and probe sets listed in Dataset S1 (34). Control experiments validated our ChIP method (Fig.…”
Section: Methodsmentioning
confidence: 99%